PENENTUAN WAKTU STANDAR PADA JASA LAUNDRY DRY AND CLEANING DI PT XYZ - Sari, Tri Novita; Arifiya, Nur; Nurfida, Anita; Hermawan, Reza (Universitas Putera Batam, 2023)
Technological advances make it easier for every human being to carry out daily activities, one example of which is washing. PT XYZ is a company engaged in dry and cleaning laundry services which offers washing and ironing services for hotels. Punctuality of service is one of the keys to success at PT XYZ. The variation in the number of orders means that PT XYZ must set a standard time or standard time, so that timely service can be maintained. Measuring working time is an estimate of the time that will be used in a job. Work measurements are carried out directly using the stopwatch time study method to obtain standard time. Based on research, it was found that the standard time for the washing process until the distribution of laundry results to each hotel was 29 hours 17 seconds